EFFECT OF GONADOTROPIN RELEASING HORMONE ON SEMEN CHARACTERISTICS IN NILI-RAVI BUFFALO BULLS - M. SAJJAD, S. ALI, S. AKHTER AND N. ULLAH1 (Pakistan Veterinary Journal, 2007)
The study was aimed at determining the effect of gonadotropin releasing hormone (GnRH) on semen characteristics in two Nili-Ravi buffalo bulls. The study was conducted in two phases. In the first phase comprising 4 weeks, the bulls were not given GnRH. In second phase comprising 4 weeks, the same bulls were given 2 ml GnRH at weekly intervals 12 hours prior to semen collection. Semen samples were collected at weekly intervals, and were evaluated for ejaculatory volume, sperm motility, sperm concentration, pH of semen and sperm abnormalities. Semen volume, sperm motility, sperm concentration and semen pH did not differ significantly in two phases of the experiment. However, sperm mid-piece and sperm tail abnormalities in phase II decreased (P<0.05) compared to phase I. In conclusion, GnRH treatment resulted in decreased sperm mid-piece and tail abnormalities in Nili-Ravi buffalo bulls.